Evaluation of groundnut (Arachis hypogaea L.) varieties, for yield and yield attributing traits in Prayagraj region - Harsh Shah; Neha Thomas; Abhinav Dayal; Prashant Kumar Rai (Annals of Agricultural Research, 2024)
A field experimental trail on groundnut was conducted during Kharif season of 2023 at field experimentation centre of Department of Genetics and Plant Breeding, Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj, U.P. to assess the extent of variability, genetic advance, heritability and correlation of different traits of 17 groundnut varieties using randomized block design with three replications. The observations were recorded on five randomly selected plants from each treatment and replication for 13 different quantitative and qualitative characters. It is concluded from the present study that the high GCV and PCV were observed for fiber content. Heritability in broad sense were recorded high for seed index followed by biological yield per plant, oil content, number of pods per plant, number of pegs per plant, oil content, harvest index, plant height and days to germination. High estimates of expected genetic advancement % mean was noticed for number of pods per plant, number of pegs per plant, fiber content, seed index and biological yield per plant. The significant variation was observed in groundnut and maximum yield was recorded by TG-37 A, SR-33. The identified promising varieties for yield component can be used as a parent in different breeding programs for yield improvement of Groundnut.